UNDERSTANDING SOCIAL MEDIA MARKETING: CONSEQUENCES ON CONSUMER ENGAGEMENT AND REPURCHASE INTENTION AMONG SMEs IN INDONESIA - Negara, Wana Pramudyawardana Kusuma; Nugroho, Sahid Susilo (Fakultas Ekonomi dan Bisnis, UNTAN, 2025)
This study examines the influence of social media marketing activities (entertainment, customization, interaction, and trendy content) on consumer engagement and repurchase intention in the context of Indonesian Small and Medium Enterprises (SMEs). Using the COBRAs (Consumers